Comparison between transcutaneous electrical nerve stimulation and metoclopramide in preventing postoperative nausea and vomiting after gastrointestinal laparoscopic surgery-A prospective and randomized study - Shalini Jain; Ruchi Agrawal; Ravi Barde; K K Arora (Asian Journal of Medical Sciences, 2023)
Background: Postoperative nausea and vomiting is a common complication after laparoscopic surgery and general anesthesia. It increases the patient’s discomfort and compromises the surgical outcome. Aims and Objectives: The study aimed to compare the effectiveness of Transcutaneous Electrical Nerve Stimulator (TENS) and Injection of Metoclopramide for the prevention of post-operative nausea and vomiting in patients undergoing gastrointestinal laparoscopic surgery. The secondary objective of the study was to find out the percentage of cases needed rescue antiemetic drug (Inj. Ondansetron) when prophylaxis failed. Materials and Methods: The study was a prospective, double-blind, randomized trial conducted at M.G.M. Medical College and M.Y. Hospital, Indore. 90 patients of 18–60 years of age, ASA physical status I-II, undergoing elective laparoscopic gastrointestinal surgery were included. Patients were allocated randomly into two equal groups. Group T received TENS (the stimulation group) at P6 acupressure point, whereas group M received an injection of Metoclopramide before induction of anesthesia. Patients in both groups were observed for 24 h postoperatively for the incidence of nausea and vomiting and the requirement for rescue antiemetic. Results: The percentage of Postoperative Nausea Vomiting (PONV) and requirement of rescue antiemetics in both the groups were comparable in the first 6 h following laparoscopic gastrointestinal surgeries (P=1.000). There was no significant difference in PONV and rescue antiemetic requirement at 24 h in both the groups. Conclusion: TENS stimulation at P6 acupressure point is comparable to injection of Metoclopramide in preventing postoperative nausea and vomiting after laparoscopic gastrointestinal surgeries.